2002
DOI: 10.1262/jrd.48.383
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Circulating Relaxin Levels during Pregnancy and Early Lactation in Japanese Monkeys (Macaca fuscata fuscata).

Abstract: Abstract. Changes in relaxin concentrations in plasma throughout pregnancy and early lactation up to one month after parturition were characterized in 10 Japanese monkeys by a heterologous radioimmunoassay (RIA) based on the porcine RIA. Plasma levels of LH/monkey chorionic gonadotropin (mCG), estradiol-17β, progesterone and immunoreactive (ir-) inhibin were also monitored for the entire period. Relaxin levels in the plasma were low before conception. An accelerated rise in plasma relaxin levels was found duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…On the other hand, fecal concentration of 17β-estradiol began to increase in the late pregnancy, remained elevated at the day of parturition and then decreased to the baseline level in the lactating period. In mammals, estrogens were increase during pregnancy, especially in late pregnancy, such as domestic ungulates (mares [15] and goats [12]), laboratory rodents (rats [25] and golden hamster [17]) or wild mammals (Japanese monkeys [16, 23], red deer [2], white-tail deer [10] and reindeer [20]). High levels of circulating estrogens promote production of oxytocin receptor [34] and relaxin receptor [6] to assist preparation of the reproductive tract for parturition and subsequently lactation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fecal concentration of 17β-estradiol began to increase in the late pregnancy, remained elevated at the day of parturition and then decreased to the baseline level in the lactating period. In mammals, estrogens were increase during pregnancy, especially in late pregnancy, such as domestic ungulates (mares [15] and goats [12]), laboratory rodents (rats [25] and golden hamster [17]) or wild mammals (Japanese monkeys [16, 23], red deer [2], white-tail deer [10] and reindeer [20]). High levels of circulating estrogens promote production of oxytocin receptor [34] and relaxin receptor [6] to assist preparation of the reproductive tract for parturition and subsequently lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous paper [5] suggested that the major source of circulating relaxin in pregnant Japanese monkeys may be the ovary, probably the corpus luteum, as in women and phesus monkeys [4,8,14]. Relaxin-containing cells have been shown immunocytochemically in the luteal cells of human term ovary [15].…”
Section: Discussionmentioning
confidence: 99%
“…W e h a v e r e c e n t l y determined plasma relaxin levels throughout pregnancy in the Japanese monkey [5]. With spontaneous parturition, a rise in plasma relaxin levels has been detected toward term [1,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relaxin acts synergistically with progesterone in maintaining pregnancy and enables the relaxation of the pelvic ligaments to aid in parturition. In the macaque, relaxin is produced by both the corpus luteum and the placenta (Shimizu et al 2002).…”
Section: Placental Hormonesmentioning
confidence: 99%